"La acción del derecho de repetición ante el tribunal de lo contencioso administrativo y la vulneración de los derechos fundamentales de las víctimas" - Herrera España, Lorena Elizabeth (2014)
This legal research work entitled "ACTION REPLAY OF LAW COURT OF THE LITIGATION AND ADMINISTRATIVE AND VIOLATION OF FUNDAMENTAL RIGHTS OF THE VICTIMS." With its respective proposal; "REFORMING THE ARTICLE 64 of the Act and Administrative Litigation What is it made in order that officials of public institutions act responsibly and to come under due process to safeguard the action replay This legal research is organized into six chapters. In the first chapter, the main part for understanding the problem and the effect was treated, it was necessary to propose the following hypothesis: "The reform of Article 64 of Law of The Contentious and Administrative Officials of the Public Institutions act responsibly to Due Process will be welcome to safeguard the action replay before the Court of Administrative Disputes ". The second chapter refers to the theoretical framework, aspects: historical, doctrinal and legal. In the third chapter the methodology used in the research described in point; methods applied types of research, population, sample techniques and instruments used in data collection. In the fourth chapter the hypothesis is tested through the research findings obtained by interviewing the subject Authorities, as well as surveys of lawyers in free practice, you know as they are violated without any consideration the rights of affected. The fifth chapter describes the conclusions and recommendations. Finally the sixth chapter discusses the proposal, objectives, description of the 'proposal, beneficiaries and social impact, etc